Monitoring and controlling humidity and pH use of LoRa in IoT-Based hydroponic planting - Usman, Usman; Achmad, Andani; Yuyun, Yuyun; Satra, Ramdan; Tribuana, Dhimas; Konate, Siaka (Bulletin of Social Informatics Theory and Application, 2024)
Indonesia, a tropical country with a growing population, has significant potential for food production but faces challenges in meeting this demand. Factors such as generation change, industrialization, and food production monopolies, as well as climate change, food security measures, and a lack of technological progress, affect productivity. Governments need to address these problems by implementing policies such as cost efficiency, supply chain management, minimum labour consumption, and effective food distribution. Food security is vital to the health and well-being of the population, and food is a vital food source to consume. Vegetables, a popular food source, are vital for health and growth. Salad, a plant used for food production, is beneficial to food production and is the main food in the modern market. Technologically speaking, food security is vital to the health and well-being of the population. Governments should focus on improving food security and ensuring that food is accessible to all. The proposed system consists of five sensors: the DHT11 sensor, the TDS meter, the humidity sensor (DS18B20), the water height sensor, and the pH meter. Data from the sensor will be stored in a cloud database via the LoRa communication network, allowing users to access data through Android applications.